Credit Availability and Asset Pricing Dynamics in Illiquid Markets: Evidence from Commercial Real Estate Markets. Issue 7 (15th September 2016) - LING, DAVID C.; NARANJO, ANDY; SCHEICK, BENJAMIN
Abstract : This article examines credit frictions and asset pricing in public and private markets with varying liquidity. We find that a tightening in credit availability is negatively related to subsequent price movements in private and public commercial real estate markets. Assets trading in illiquid segments of these markets are also susceptible to a feedback effect whereby changes in asset prices predict subsequent changes in credit availability. Controlling for investor demand, our findings suggest credit constraints play an economically significant asset pricing role in markets that are both highly levered and relatively illiquid.